(untitled) (Journal of actual problems of jurisprudence, 2020)
Until recently, due attention has not been paid to issues of professional ethics and morality of justice workers as an important element of the culture of criminal proceedings. However, without the implementation of certain judicial-ethical rules, criminal procedure activity will not be able to fulfill the tasks formulated in the law. Observance by an expert of not only legal, but also moral standards is a certain guarantee of the reliability of his conclusions, the validity of his conclusion. The need for a thorough study of the moral principles of a forensic expert is determined by the very essence of the expert examination as a way of obtaining evidence through the use of special knowledge, and also by the great role that examination plays in legal proceedings. The purpose of the article is to analyze the current state of this problem from the point of view of ethics, law and psychology. Based on modern scientific methods and a wide range of foreign sources and legislative acts of different countries, an analysis of the global discussion on the issue of professional ethics and morality of experts is carried out. The application of general scientific methods made it possible to compare the domestic and international methodology of work. The classification of states based on the criteria of professional ethics and morality. The examples of the legal framework on the professional ethics of experts examined issues of legal regulation. As a result of the study, conclusions are drawn about the legal personality of the expert and his legal awareness. In particular, the assumption is justified on how the legislation of the Republic of Kazakhstan should regulate these issues in an ethically consistent manner. Key words: law, forensic expert, professional ethics, legal awareness, inner conviction.